HUBUNGAN ANTARA BUDAYA ORGANISASI DAN MOTIVASI DENGAN PENGEMBANGAN KARIR PEGAWAI DI BIRO KEPEGAWAIAN DAN ORGANISASI TATALAKSANA KEMENTERIAN PEKERJAAN UMUM JAKARTA SELATAN - Handaru, Agung Wahyu; Ajiningtyasasih, Natalia (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2011)
The research AIMS: 1) to analyze the relationship between organizational behavior and employee career development in the Bureau of Human Resources and Organization Officer of the Ministry of Public Works of South Jakarta. 2) to analyze the relationship between motivation and employee career development in the Bureau of Human Resources and Organization Officer of the Ministry of Public Works of South Jakarta. The numbers of samples are 47 staffs which are represented from every division in Bureau of Human Resources and Organization Officer Ministry of Public Works of South Jakarta. The data collecting is conducted by questionnaire. Correlation analysis is used to analyze the data and to answer the Relationship Between variables X and Y. The result of analysis shows that the variable is organizational culture have a positive and significant relationship with career development variable (r = 0.392, P = 0.000) with a low rate (weak) relationship. Motivation variable have a positive and significant relationship with career development variable (r = 0.486, P = 0.000) with high rate (strong) relationship. Keywords: organizational culture, motivation, career development